Distribution of fish in river is controlled by physico-chemical properties of the water which is affected by land-use complexity and intensity of human intervention. A study on fish distribution was carried out in the upper Citarum River to map the effects of physio-chemical properties on habitat use. A survey was conducted to collect fish and to measure the water quality both on dry and rainy season. The result showed that distribution of the fish, in general, represented their adaptive respons - . SUNARDI; KEUKEU KANIAWATI; TEGUH HUSODO; DESAK MADE MALINI; ANNISA JOVIANI ASTARI (Bogor Agricultural University, Indonesia, 2012)
Distribution of fish in river is controlled by physico-chemical properties of the water which is affected by land-use complexity and intensity of human intervention. A study on fish distribution was carried out in the upper Citarum River to map the effects of physio-chemical properties on habitat use. A survey was conducted to collect fish and to measure the water quality both on dry and rainy season. The result showed that distribution of the fish, in general, represented their adaptive response to physico-chemical properties. The river environment could be grouped into two categories: (i) clean and relatively unpolluted sites, which associated with high DO and water current, and (ii) polluted sites characterized by low DO, high COD, BOD, water temperature, NO3, PO4, H2S, NH3, and surfactant. Fish inhabiting the first sites were Xiphophorus helleri, Punctius binotatus, Xiphophorus maculatus, and Oreochromis mossambicus. Meanwhile, the latter sites were inhabited by Liposarcus pardalis, Trichogaster trichopterus, and Poecilia reticulata. Knowledge about fish distribution in association with the pysico-chemical properties of water is crucial especially for the river management.